Peningkatan Keterampilan dan Kewirausahaan Pemuda Putus Sekolah melalui Pelatihan Pengelasan sebagai Usaha Meningkatkan Kesejahteraan Masyarakat - Made Mara (Universitas Mataram, 2018)
Escalating the quality of human resources is an important part of the development process of a nation. The quality of human resources is a major factor to support the nation's competitiveness in the global competition. Moreover, Indonesia as a developing country is facing the complexity of the problems based on destitution, lagging behind of education, economy, culture and high levels of unemployment and other social problems. Based on the above consideration, its need to pay a serious attention on the development of the young generation to guide and provide them by vocational skills that is able to empowering them towards more productive direction. Skills education and welding training are conducted in conjunction with youth groups. The target of this project is the community in general, especially the youth. At the end of this project, it is desirable that the skills gained from this welding training can be used in generating their own job.